A masked initiation region in retinoblastoma protein regulates its proteasomal degradation - Tomita, Takuya (Nat Commun, 2020)
Retinoblastoma protein (Rb) is a tumor suppressor that binds and represses E2F transcription factors. In cervical cancer cells, human papilloma virus (HPV) protein E7 binds to Rb, releasing it from E2F to promote cell cycle progression, and inducing ubiquitination of Rb. E7-mediated proteasomal degradation of Rb requires action by another protease, calpain, which cleaves Rb after Lys 810. However, it is not clear why cleavage is required for Rb degradation. Here, we report that the proteasome cannot initiate degradation efficiently on full-length Rb. Calpain cleavage exposes a region that is recognized by the proteasome, leading to rapid proteolysis of Rb. These findings identify a mechanism for regulating protein stability by controlling initiation and provide a better understanding of the molecular mechanism underlying transformation by HPV.